Description of Scolomys melanops nest (Rodentia, Cricetidae) and its relationship with Lepidocaryum tenue (Arecales, Arecaceae) - Rengifo, Edgardo M. (2012)
We describe the nest of Scolomys melanops, (Rodentia: Cricetidae) found in low hill habitats in northeastern Peru. We identified three structures in the nest: a) an orifice of access and exit; b) a tunnel and c) roosting area. In the last structure, we found fruit and fiber remains of peduncle and stems of Lepidocaryum tenue (Arecales: Arecaceae) “Irapay”. Based on the vegetal remains found in the nest, we suggest the existence of a predation relationship between the rodent Scolomys melanops and the palm Lepidocaryum tenue.